A Novel bis-indole Alkaloid from the Flowers of Rauvolfia yunnanensis Tsiang and its Antihypertension Activity - Wang, Haibo; Liu, Xikui (Letters in Organic Chemistry, 2020)
A novel bis-indole alkaloid was isolated from the flowers of Rauvolfia Yunnanensis Tsiang. Its structure was elucidated as 10,11´- dimethoxy-11,10´-bis-[N(a)-methyl deacetyldeformyl- 1,2- dihydro akuammiline(2β)] (1) on the basis of spectroscopic analysis, including 1D and 2D NMR techniques as well as HRESI-MS and comparison with data from the literature. The bis-indole alkaloid displayed more potent antihypertension activity and much lower hepatotoxicity in vivo than Reserpine.
Keywords: Rauvolfia yunnanensis